Implementasi Gerakan Literasi Sekolah Sebagai Bentuk Karakter Mandiri Pada Siswa Di Mi Muhammadiyah 4 Brangsi - Ula, Rahmatul; Nur Kholifah, Fitri Ardiha; Ratna sari, Zuli; Setiawan, Agung (Fakultas Agama Islam, 2024)
This study aims to determine the implementation of the school literacy movement as a form of independent character in students at MI Muhammadiyah 4 Brangsi. Most students in Indonesia experience a lack of interest in reading. One way to overcome the lack of interest in reading is by optimizing the school literacy movement. The school literacy movement is an effort to shape the character of students. Character education is an effort to prepare a generation with a social, religious, cultured, and virtuous sense of words, deeds, behaviour, morals, and independent personality. This research method is qualitative with a descriptive approach. The research data sources are primary and secondary data with data collection techniques through observation, interviews and documentation. Data analysis used includes data reduction, data presentation and conclusion drawing. The results showed that implementing the school literacy movement fostered student's independence. The implementation of the school literacy movement in students at MI Muhammadiyah 4 Brangsi is divided into three stages, namely the habituation stage, the habituation stage, and the literacy stage. The implementation of this school literacy movement is carried out routinely every two weeks. It can be concluded that with the literacy movement, the literacy movement can instil independent character in students. In implementation, it needs to be invested in students to introduce reading habits from an early age and get used to reading for 15 minutes according to the existing schedule.